Hubungan Antara Technostress Dengan Work Life Balance Pada Karyawan di PT X - Rahel Silitonga; Intan Kristiani Lature; Ivanka Natalia Silalahi; Eunike Ekanina Br Ginting; Mukhaira El Akmal; Rianda Elvinawanty (Jayapangus Press, 2026)
This study aims to analyze the relationship between technostress and work-life balance among employees at PT X in the digital era. A quantitative approach was employed involving 134 employees selected through purposive sampling. Data were collected using Likert-scale questionnaires consisting of a technostress scale (25 valid items) and a work-life balance scale (27 valid items). Data analysis was conducted using Pearson Product-Moment correlation. The results indicate a significant positive relationship between technostress and work-life balance (r = 0.820; p < 0.001), leading to the rejection of the initial hypothesis that proposed a negative relationship. Technostress contributed 67.2% to work-life balance, while the remaining variance was influenced by other factors. Categorization results show that the majority of respondents fall into the moderate category for both technostress (78.4%) and work-life balance (65.4%). These findings suggest the presence of effective adaptation mechanisms or coping strategies, where technology is perceived as a supportive tool in integrating work demands and personal life.